Uncertain choices with asymmetric information: how clear evidence and ambiguity interact? - Amir Hossein Tehrani-Safa; Amir Hossein Tehrani-Safa; Atiye Sarabi-Jamab; Abdol-Hossein Vahabie; Abdol-Hossein Vahabie; Babak Nadjar Araabi (Frontiers in Psychology)
Real-world decisions often involve partial ambiguity, where the complete picture of potential risks is unclear. In such situations, individuals must make choices by balancing the value of available information against the uncertainty of unknown risks. Our study investigates this challenge by examining how people navigate the trade-off between the favorability of limited evidence and the degree of ambiguity when making decisions under partial ambiguity. Participants (n = 77) engaged in a task where the level of ambiguity (small, medium, and large) and the favorability of the evidence (asymmetrically positive, neutral, and asymmetrically negative) were manipulated in a 3 × 3 design. We measured their attitude of ambiguity in each condition. The key finding reveals a bias in how participants perceived the unknown. They reacted to the unknown differently depending on the initial clues, filling in the missing information in a way that contradicted the evidence. When faced with positive evidence, participants were less tolerant of ambiguity than negative evidence. This means people were more careful when they received good news but less cautious when they received bad news. This bias was particularly pronounced when the ambiguity was low.